A naturally occurring variation in the BrMAM-3 gene is associated with aliphatic glucosinolate accumulation in Brassica rapa leaves. Issue 1 (December 2018) - Zhang, Jifang; Wang, Hui; Liu, Zhiyuan; Liang, Jianli; Wu, Jian; Cheng, Feng; Mei, Shiyong; Wang, Xiaowu
Abstract Glucosinolate profiles significantly vary amongBrassica rapa genotypes. However, the molecular basis of these variations is largely unknown. In this study, we investigated a major quantitative trait locus (QTL) controlling aliphatic glucosinolate accumulation inB. rapa leaves. The QTL, which encompasses three tandemMAM genes and twoMYB genes, was detected in two BC2 DH populations. Among the five-candidate genes, only the expression level ofBrMAM-3 (Bra013007) was significantly correlated with the accumulation of aliphatic glucosinolates inB. rapa leaves. We identified a naturally occurring insertion within exon 1 ofBrMAM-3, which is predicted to be a loss-of-function mutation, as confirmed by qRT-PCR. We determined that the loss of function was associated with the low glucosinolate content inB. rapa accessions. Furthermore, overexpressing theBrMAM-3 gene resulted in an increase in total aliphatic glucosinolates inArabidopsis transgenic lines. Our study provides insights into the molecular mechanism underlying the accumulation of aliphatic glucosinolates inB. rapa leaves, thereby facilitating in the manipulation of total aliphatic glucosinolate content inBrassica crops. Giving vegetables a nutritional upgrade The identification of a gene controlling the production of a critical class of plant metabolites could enable researchers to engineer healthier crops. Vegetables such as cabbage and broccoli generate various glucosinolates as a defense mechanism against pests and disease. But these molecules also have nutritional and medicinal value, and researchers led by Xiaowu Wang at the Chinese Academy of Agricultural Sciences have homed in on a key step in their manufacturing process. Working with the model speciesBrassica rapa, Wang and colleagues learned that a gene calledBrMAM-3 performs the critical first step in synthesizing a major class of glucosinolates. Manipulation of this gene as well as those encoding the enzymes that subsequently shape the functional characteristics of the resulting glucosinolates could yield enhanced vegetables that are even healthier for consumers.